Suicide mortality in women of fertile age - Teixeira , Larissa de Morais (2020)
The study aims to understand the epidemiological profile of suicide mortality in women of childbearing age in a state in northeastern Brazil, from 2009 to 2018, through a quantitative approach, with a descriptive and ecological study, using a source of information. secondary public data. 12,012 deaths of women of childbearing age were identified, of which 216 deaths (1.8%) were due to suicide, the majority (33.3%) aged 20 to 29 years, brown (83.3% ), with 1 to 7 years of study (13.4%), single (63%), with (44.4%) of the deaths occurring at the residence itself, the majority (50.5%) due to self-harm caused by hanging, strangulation and suffocation. However, suicide mortality in Alagoas may be even higher in view of underreporting, due to the social stigma that contributes to the omission of cases. Finally, it is concluded that the epidemiological profile of suicide mortality in women of childbearing age in the state of Alagoas proved to be similar to the Brazilian profile, and it is essential to adopt effective strategies for the prevention of suicide, with intersectoral and multidisciplinary actions that ensure early assistance and intervention to women facing this reality.